Estudo da viabilidade técnica do reaproveitamento de altos teores de fibras de poli(para-aramida) como reforço mecânico em poliamida 66 - Bello, Thômas Scarassati (Universidade Federal de São Carlos, 2018)
Responsible for an annual demand higher than 70 millions of tons, the poly(para- aramide) fibers are being widely used in the safety, automobilist, aeronautic, and petroleum industries, due to their attractive mechanical, chemical, and thermal properties. However, these fibers cannot be recycled by conventional processes and have to be incinerated or discarded in specific landfills. In order to achieve new applications for their industrial wastes, this project had as main goal the study of technical feasibility in the reuse of high content of poly(para-aramide) fibers as mechanical reinforcement in polyamide 66. The composites were produced by twin-screw extrusion in contents of 10 and 20%, and the screw speed and fiber feed zone were also modified. In addition, the poly(para-aramide) fibers have low adhesion with polymers, and can be even lower with finishing substances from industrial processes. For this reason, the removal of these substances was another condition studied in this work. According to the analyses, a continuous and stable processing is hampered by the high fiber specific volume. The finishing substances removal had a detrimental effect in the process due to increasing on fiber-fiber friction and did not affect the PA66-fiber adhesion. The results have shown that composition and processing conditions did not affect fiber length, which was above the critical length. At the same time, these variables effects were significant on PA66 degradation, which were determinant on composite final properties. It was possible to increase the mechanical properties, and, under certain conditions, it was higher than the commercial composites of PA66/poly(para-aramide).
Study of technical feasibility in the reuse of high content of poly(para-aramide) fibers as mechanical reinforcement in polyamide 66
Keywords: Compósito; Poli(para-aramida); Processamento; Degradação; Composite; Poly(para-aramide); Processing; Degradation; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA